Teachers' Efforts to Increase Students' Spiritual Intelligence Through Congregational Dhuhr Prayer Activities at SMP Karya Bhakti Medan - Sihotang, Agung; Sami'in, Sami'in; Pasaribu, Mei Sandi (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
The aims of this research are (1) To find out activities that increase students' spiritual intelligence, (2) To find out the efforts made by teachers to increase students' spiritual intelligence, and (3) To find out the contribution of congregational midday prayer activities to increasing students' spiritual intelligence. This research uses a qualitative approach. Data collection techniques in this research used observation, interview and documentation techniques. Meanwhile, data analysis uses the Miles and Huberman concept which includes data reduction, data presentation, and drawing conclusions. To check the validity of the data, use diligent/constant observation and triagulation. The results of this research can be concluded as follows: (1) Activities that increase students' spiritual intelligence such as midday prayers in congregation, dhuha prayers in congregation, tadarus Al-Qur'an and reading asmaul husna so that they can be useful anywhere and anytime. (2) Efforts made by teachers to improve students' spirituality through good planning in congregational midday prayers starting from preparation, implementation and results of student changes. The teacher felt an increase in the students' spiritual intelligence, seeing the increasing enthusiasm of the students in participating in this congregational midday prayer activity. (3) There is a congregational midday prayer activity at SMP Karya Bhakti Medan is able to increase students' spiritual intelligence with indicators: (a) Students are orderly and disciplined in congregational prayers (b) Increased self-awareness for worship (c) Improved good relations between teachers and students (d) A sense of responsibility arises answer to students.